2011
DOI: 10.1007/s12640-011-9239-x
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Low Alcohol and Nicotine Combinations in SH-SY5Y Cells are Apoptotically Mediated

Abstract: It is well established that combination of heavy drinking and smoking has severe health consequences. However, at relatively low concentrations, both alcohol and nicotine may have beneficial effects including neuroprotection. Thus, protective effects of low alcohol concentration against beta-amyloid-induced toxicity in organotypic hippocampal slices and protective effects of nicotine against salsolinol-induced toxicity in human-derived neuroblastoma cells (SH-SY5Y) have been reported. In this study, we sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 23 publications
4
31
0
Order By: Relevance
“…Nicotine/nicotinic agonists have been suggested to have therapeutic potential in neuropsychiatric and neurodegenerative diseases, particularly in Parkinson's disease (PD) (Quik et al 2015;Tizabi 2016;Tizabi and Getachew 2017). We had also observed protective effects of low nicotine concentration (e.g., 10 μM) against salsolinol-induced toxicity in SH-SY5Y cells (Copeland et al 2007;Ramlochansingh et al 2011). Curiously, however, when we combined low alcohol with low nicotine concentrations, contrary to our expectation of an additive protective effect, a significant toxicity, with or without salsolinol, was noted (Ramlochansingh et al 2011).…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…Nicotine/nicotinic agonists have been suggested to have therapeutic potential in neuropsychiatric and neurodegenerative diseases, particularly in Parkinson's disease (PD) (Quik et al 2015;Tizabi 2016;Tizabi and Getachew 2017). We had also observed protective effects of low nicotine concentration (e.g., 10 μM) against salsolinol-induced toxicity in SH-SY5Y cells (Copeland et al 2007;Ramlochansingh et al 2011). Curiously, however, when we combined low alcohol with low nicotine concentrations, contrary to our expectation of an additive protective effect, a significant toxicity, with or without salsolinol, was noted (Ramlochansingh et al 2011).…”
Section: Introductionmentioning
confidence: 65%
“…We had also observed protective effects of low nicotine concentration (e.g., 10 μM) against salsolinol-induced toxicity in SH-SY5Y cells (Copeland et al 2007;Ramlochansingh et al 2011). Curiously, however, when we combined low alcohol with low nicotine concentrations, contrary to our expectation of an additive protective effect, a significant toxicity, with or without salsolinol, was noted (Ramlochansingh et al 2011).…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Moreover, in vitro and in vivo studies have shown that nicotine may protect against nigrostriatal damage induced by various compounds. Thus, in Parkinson’s disease cell models, nicotine protects against endogenous substances such as salsolinol and aminochrome that selectively damage dopaminergic cells (Copeland et al 2005, 2007; Das and Tizabi 2009; Ramlochansingh et al 2011; Munoz et al 2012). Similarly in animal studies, including non-human primates, it has been shown that nicotine delays Parkinson’s disease-like symptoms induced by MPTP (Quik et al 2006, 2009, 2014).…”
Section: Nicotinementioning
confidence: 99%